Psychological Peculiarities of Stigmatization of Otherness and its Display during the Process of Media Communication - Husiev, Ihor (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article outlines theoretical developments in the field of stigmatization. The stages of development of stigmatization are given: selection and «marking» of the person which differs from conditional norm; assigning it negative qualities in accordance with the existing in this culture ideas about certain features; assigning it to a certain «category» that opposes society and further reducing the social status of this person. Attention is paid to the process of self-stigmatization – a person’s awareness of the presence of a certain feature that distinguishes him from the majority, assimilation and application of myths about his «otherness», with further distancing from potential stigmatizers. This leads to a decrease in social status, self-esteem, which in turn increases stigma. Two separate surveys were conducted; one among the general population, and the other about the peculiarities of the stigmatization of stigmatized minorities’ own stigma was studied during a survey of LGBT and HIV activists. The total sample was 687, of whom 493 were the general population and 194 were members of stigmatized minorities. The display of stigmatization was investigated due to the prevalence of cyberbullying using different media channels. In total, 71 % of respondents were victims of cyberbullying (from isolated cases (49 %) to persistent harassment (4 %). The most common victims of cyberbullying are men, and among activists – HIV activists. Activists often face such acts of cyberbullying as insults in comments to news and on Twitter, threats on Facebook, intimidation on forums. Only 20 % of cyberbullying victims turned to various institutions to stop harassment.